ANALYZING THE MEANING OF CAPITAL FOR FARMERS - Rahma, Fia; Triyuwono, Iwan; Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2019)
The objective of this research is to find out the meaning of capital for farmers, by using the logical reasoning analysis of bayani, burhani, and irfani initiated by Mohammad Abed Al Jabiri (1991). The process of finding out the meaning of capital by farmers is conducted by knowing and analyzing the capital of the informants obtained through in-depth interview and observation, using three types of logical reasoning which are bayani, burhani, and irfani. Through bayani logical reasoning, the researchers got the symbol of the meaning of capital conveyed by the informants and is examined by the text approach. Moreover, through burhani logical reasoning, analysis, the researchers explored the facts, conditions, and background of the informants' lives. The final step of data analysis in this research was gained through the irfani logical reasoning approach that was applied by the synchronization process of all information obtained using the researchersâ€™ clarity of conscience to be able to draw a comprehensive conclusion. This research found the meaning of capital for Smartani group farmers is combination material capital and the determination to apply the science and experience in managing the resources they own well, by maintaining relationship with colleagues and community for the continuity of the farming business.Â Keywords: capital, farmers, bayani, burhani, irfaniÂ